2015
DOI: 10.14295/cs.v6i3.670
|View full text |Cite
|
Sign up to set email alerts
|

Época e intensidade de poda no desenvolvimento e produção de amoreira-preta cv. Xavante cultivada em sistema orgânico

Abstract: The practice of winter pruning, held in temperate fruit, has great influence on the development and production of these crops. Changes in pruning system may result in significant changes in the time of harvest, yield and fruit quality.This study aimed to evaluate the effects of time and intensity of pruning in the development and production of blackberry cv. Xavante in organic production system. The experiment was conducted during the crop year 2009/2010 and 2010/2011 in the experimental orchard of the State U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 13 publications
1
4
0
1
Order By: Relevance
“…As for the fresh mass of the fruits (Table 2), an important characteristic for their marketing in natura (Ferreira et al, 2016), only the treatment with 4 stems differed from the others, with the lowest mass, however the results found in this work, are similar to those reported by Marchi et al (2015), in Guarapuava, PR, Brazil, in which they evaluated the time and intensity of pruning in the development of blackberry cv. Xavante, and obtained an average fruit mass of 4.1 g in the 2010/201 harvest.…”
Section: /6supporting
confidence: 84%
See 3 more Smart Citations
“…As for the fresh mass of the fruits (Table 2), an important characteristic for their marketing in natura (Ferreira et al, 2016), only the treatment with 4 stems differed from the others, with the lowest mass, however the results found in this work, are similar to those reported by Marchi et al (2015), in Guarapuava, PR, Brazil, in which they evaluated the time and intensity of pruning in the development of blackberry cv. Xavante, and obtained an average fruit mass of 4.1 g in the 2010/201 harvest.…”
Section: /6supporting
confidence: 84%
“…Regarding the number of fruits per plant (Table 2), it was observed that the treatment with 8 stems per plant was the most satisfactory, considering that these did not lose in mass. More intense pruning can result in lower productivity, due to the reduction of floral buds (Calai et al, 2020), however, for all treatments, the number of fruits per plant was relatively low when compared to other studies, such as Broetto et al (2009) and Marchi et al (2015). This may have occurred due to atypical conditions during the execution of the work, in which the plants took about 45 days after pruning to start flowering, when, during this period, the days were already hot, so it was necessary to use irrigation, which resulted in plants with high vegetative vigor, and consequent reduction of the productive period.…”
Section: /6mentioning
confidence: 51%
See 2 more Smart Citations
“…A produtividade obtida nesta pesquisa atende as expectativas para a amora-preta 'Tupy' pois, segundo Antunes et al (2014), a produtividade média brasileira varia de 10.600 Kg ha -1 a 16.300 Kg ha -1 , superando os 5.169 Kg ha -1 obtidos por Antunes et al (2010), na mesma região e corroboram com o resultados observados por Campagnolo e Pio ( 2012), para a região oeste do Paraná, os quais observaram que poda realizada em meados de julho é mais indicada do que poda tardia que pode prejudicar o desempenho produtivo da cultura, devido aos maiores riscos de exposição da cultura ao déficit hídrico e granizo. Ainda, em duas safras de cultivo da amora 'Xavante', em Guarapuava, no estado do Paraná, Marchi et al (2015) observaram que o atraso da poda, de início para o fim do mês de agosto, resultou em decréscimo na produtividade na ordem de 19% numa safra e de 24% safra seguinte.…”
Section: Resultsunclassified